2022
DOI: 10.1038/s41598-022-12660-0
|View full text |Cite
|
Sign up to set email alerts
|

The value of histological examination in the diagnosis of tuberculous lymphadenitis in the era of rapid molecular diagnosis

Abstract: Extrapulmonary tuberculosis often poses a diagnostic challenge. This study aimed to assess the value of histological examination in diagnosing tuberculous lymphadenitis (LNTB) when performed simultaneously with rapid molecular assay (Xpert MTB/RIF) testing. People presumed to have LNTB were prospectively enrolled in a tertiary care hospital. Excision biopsy was performed and tested by histology, Xpert, and culture. Of 390 lymph nodes, 11 (2.8%) were positive by AFB microscopy, 124 (31.8%) by Xpert, 137 (35.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…Obtaining appropriate specimens for histological examinations was recommended for a patient with suspected EPTB ( Hopewell et al., 2006 ; Migliori et al., 2018 ). In general, histopathology is highly sensitive (86%-95% reported; HE: 92.4% [85.7-96.1] and AFB: 81.7% [73.2-88.0] in this study), but not very specific (64%-92% reported; HE: 71.3% [61.0-79.7] and AFB: 73.3% [63.1-81.5] in this study), for the diagnosis of tuberculosis ( Bennani et al., 2019 ; Shen et al., 2022 ; Tahseen et al., 2022 ).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Obtaining appropriate specimens for histological examinations was recommended for a patient with suspected EPTB ( Hopewell et al., 2006 ; Migliori et al., 2018 ). In general, histopathology is highly sensitive (86%-95% reported; HE: 92.4% [85.7-96.1] and AFB: 81.7% [73.2-88.0] in this study), but not very specific (64%-92% reported; HE: 71.3% [61.0-79.7] and AFB: 73.3% [63.1-81.5] in this study), for the diagnosis of tuberculosis ( Bennani et al., 2019 ; Shen et al., 2022 ; Tahseen et al., 2022 ).…”
Section: Discussioncontrasting
confidence: 59%
“…Auramine O staining is not able to distinguish between dead or live bacteria, but culture only detects viable bacteria, thus NaOH used in sample pre-treatment may result in lower sensitivity of culture than smear. Obtaining appropriate specimens for histological examinations was recommended for a patient with suspected EPTB (Hopewell et al, 2006;Migliori et al, 2018) : 73.3% [63.1-81.5] in this study), for the diagnosis of tuberculosis (Bennani et al, 2019;Shen et al, 2022;Tahseen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a la histopatología, ésta dará el diagnóstico certero en hasta el 88% de los casos, encontrándose hallazgos característicos al cultivo como lo son la presencia de granulomas caseificantes, presencia de BAAR, células gigantes multinucleadas y células epitelioides 9,11,28 .…”
Section: Diagnósticounclassified
“…Epithelioid cells may also fuse to form multinucleated giant cells, and central necrosis is evident in necrotizing granulomas. Caseous necrosis and granulomatous formation are two specific pathological features of LN TB (6,7).…”
Section: Introductionmentioning
confidence: 99%